Donor and Recipient Age-Mismatches: The Potential of Transferring Senescence - Iske, Jasper; Matsunaga, Tomohisa; Zhou, Hao; Tullius, Stefan G. (Frontiers in Immunology, 2021)
In transplantation, donor and recipients frequently differ in age. Senescent cells accumulate in donor organs with aging and have the potential to promote senescence in adjacent cells when transferred into recipient animals. Characteristically, senescent cells secrete a myriad of pro-inflammatory, soluble molecules as part of their distinct secretory phenotype that have been shown to drive senescence and age-related co-morbidities. Preliminary own data show that the transplantation of old organs limits the physical reserve of recipient animals. Here, we review how organ age may affect transplant recipients and discuss the potential of accelerated aging.